The Evaluation of Critical Velocity and Dynamic Loads in Multiphase Flows - Ismayilova, F.B.; Shukurlu, M.F. (Herald of Azerbaijan Engineering Academy, 2025)
In the article, the matter of estimation of critical velocity and dynamic loads was considered during the movement of multiphase flows through pipelines, taking into account their main feature. It is determined how the critical velocity changes along the cross-section for different structural forms of the flow formed regarding the interaction of the phases. Based on the calculation of dynamic loads in multiphase flows based on the change of the critical velocity, it was determined that these loads are less for the movement in the form of a dispersed-bubble structure than in the stratified-plug structures. It was determined that the minimum value of the critical velocity corresponds to the maximum value of the pressure gradient.